Efficacy and Safety Outcome Domains and Outcome Measures in Systematic Reviews of Neuropathic Pain Conditions. Issue 7 (July 2018) - Dosenovic, Svjetlana; Jelicic Kadic, Antonia; Jeric, Milka; Boric, Matija; Markovic, Domagoj; Vucic, Katarina; Puljak, Livia
Abstract : Objectives: Heterogeneity of outcome domains, used in interventional trials and systematic reviews (SRs) for neuropathic pain (NeuP), makes decisions on the comparative effectiveness of available treatments difficult. This study analyzed outcome domains and measures used in SRs of randomized controlled trials on efficacy and safety of interventions for NeuP and compared them with the core outcome set (COS) and core outcome measures (COMs) for chronic pain recommended by the Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT). Methods: Five electronic databases were searched to find SRs of interventions for NeuP. Outcome domains and measures were independently extracted by 2 authors, and compared against the IMMPACT-recommended COS and COMs. Outcome domains specified in the methods and reported in the results were also compared. Results: Ninety-seven SRs were analyzed. The 2 core domains most frequently specified in the methods and reported in the results of SRs were pain and symptoms and adverse events. Pain intensity was mostly assessed with Visual Analog Scale (n=59) and Numerical Rating Scale (n=29). The incidence (n=70) and severity (n=60) were most commonly reported for adverse events. There were 240 different outcome measures used for the assessment of treatment efficacy and safety. Conclusions: Authors of SRs in the field of NeuP insufficiently use relevant recommended COS and COMs for chronic pain. More effort should be put into the implementation of COS to ensure that the study results can be compared and combined. There is a need for defining core outcome domains and measures specific for NeuP. Abstract : Supplemental Digital Content is available in the text.